Impact assessment of the COVID-19 on trade between Eastern Europe and China - Megits, Nikolay; Neskorodieva, Inna; Schuster, Julian (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
The high-risk of the rapidly spreading COVID-19 virus worldwide created a necessity for developing a diagnostic tool designed to predict economic development, considering the risks of spreading the coronavirus epidemic. In the proposed research, China is selected strategically due to the U.S. "Buy American" trade policy. Also, the European Union presents various trade barriers for countries of Eastern Europe. The risk-versus-economic efficiency study is performed based on Fibonacci law utilizing trade-dynamic indicators with incorporating the SIR-model used to predict the dynamics of COVID-19 cases in the region. The research was performed based on data collected for the period of March-July 2020. As a result, a scientific model to predict the dynamics of trade volume between China and selected Eastern European countries is developed. The results obtained have a practical application and can be used for government institutions and economic agencies to determine their nation’s short- and long-term international trade strategy.